Peran Keluarga dalam Merawat Pasien Lansia Penderita Hipertensi dengan Tekanan Darah Tinggi - Maryati , Heni; Supriliyah Praningsih; Fitri Firranda Nurmalisyah; Siswati (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Objective: Hypertension is a condition of persistently elevated arterial blood pressure and continues to be a major global health problem. The WHO estimates that by 2025, 1.5 billion people will suffer from hypertension, and 10.44 million people are predicted to die from hypertension and its complications each year. The role of the family is crucial in managing hypertension. Families play a crucial role as caregivers in improving the health status of their sick family members, as they play a crucial role in maintaining the health of those with hypertension. This study aimed analyzing the role of family in caring for elderly hypertension on blood pressure Methods: This research is a correlational study with a cross-sectional design using purposive sampling. The subjects were 46 elderly people with hypertension in Puton Village, Diwek District, Jombang Regency, according to the inclusion criteria for the 2025 study. The instruments used were the role of the family in caring for elderly people with hypertension using questionnaires and interviews (food selection, physical activity, stress management, referral to health facilities), and blood pressure measurements. Data were analyzed using coding, editing, tabulation, and scoring, and statistical tests were performed using the Chi Square test. Results: Based on the research results, it was shown that out of 47 respondents, 26 (55.3%) respondents had a not good family role in caring for elderly people with hypertension. Classification of hypertension based on blood pressure values, namely the majority (63.84) in the grade 2 hypertension category. Chi Square test for using SPSS yielded a p value of 0.02 less than 0.05 indicating correlation between the role of family in caring for elderly hypertension on blood pressure Conclusion: The role of the family in motivating the elderly with hypertension through exercise, regulating diet, encouraging them to control their blood pressure and taking medication, and regularly visiting health services can control blood pressure. The greater the role of the family, the better the quality of life of the elderly, which can be seen from the number of elderly whose blood pressure is controlled.